PENGEMBANGAN MODUL YANG DIAWALI PETA KONSEP PADA MATERI SISTEM EKSKRESI UNTUK SMA - Putri, Elsa Harkhian; Risdawati, M.Si., Renny; Susanti, Diana (STKIP PGRI Sumbar, 2014)
ABSTRACT Modul is a form teaching material which stake to learned with autonomous by the students. The result of observation in SMAN 6 Padang, in that school there is no good modul. Based on the cases, have been conducted by development of modul that begin with concept map in exretion system for SMA class XI. The purpose of this research to resulted modul that begin with concept map in exretion system material which valid and practice. The research is development research with use the development of modle 4-D which consist of define step, design step, develop step and disseminate step, disseminate step do not conducted because the limit of the researcher. The subject of the research consists of 4 people validator, and for test practicalities 2 people of biology teacher and 35 students of SMAN 6 Padang class XII in ekskresi system material. The data of the research is primary data which obtained from questionnaire validity and practicalities, however in analysis with descriptive analysis. The result of analysis data showed that modul that begin with concept map had the average 87,27% with valid category. The practicalities by the teacher and students to be obtained average 98,33% and 90,09%. Both of them to be categories very practice. In conclusion modul teaching material that begin with concept map in exretion system material for SMA which resulted fulfill criteria that valid and very practice.